Effect of multidimensional lifestyle intervention on fitness and adiposity in predominantly migrant preschool children (Ballabeina): cluster randomised controlled trial. (13th October 2011) - Puder, J J; Marques-Vidal, P; Schindler, C; Zahner, L; Niederer, I; Bürgi, F; Ebenegger, V; Nydegger, A; Kriemler, S
Abstract : Objective To test the effect of a multidimensional lifestyle intervention on aerobic fitness and adiposity in predominantly migrant preschool children. Design Cluster randomised controlled single blinded trial (Ballabeina study) over one school year; randomisation was performed after stratification for linguistic region. Setting 40 preschool classes in areas with a high migrant population in the German and French speaking regions of Switzerland. Participants 652 of the 727 preschool children had informed consent and were present for baseline measures (mean age 5.1 years (SD 0.7), 72% migrants of multicultural origins). No children withdrew, but 26 moved away. Intervention The multidimensional culturally tailored lifestyle intervention included a physical activity programme, lessons on nutrition, media use (use of television and computers), and sleep and adaptation of the built environment of the preschool class. It lasted from August 2008 to June 2009. Main outcome measures Primary outcomes were aerobic fitness (20 m shuttle run test) and body mass index (BMI). Secondary outcomes included motor agility, balance, percentage body fat, waist circumference, physical activity, eating habits, media use, sleep, psychological health, and cognitive abilities. Results Compared with controls, children in the intervention group had an increase in aerobic fitness at the end of the intervention (adjusted mean difference: 0.32 stages (95% confidence interval 0.07 to 0.57; P=0.01) but no difference in BMI (−0.07 kg/m 2, −0.19 to 0.06; P=0.31). Relative to controls, children in the intervention group had beneficial effects in motor agility (−0.54 s, −0.90 to −0.17; P=0.004), percentage body fat (−1.1%, −2.0 to −0.2; P=0.02), and waist circumference (−1.0 cm, −1.6 to −0.4; P=0.001). There were also significant benefits in the intervention group in reported physical activity, media use, and eating habits, but not in the remaining secondary outcomes. Conclusions A multidimensional intervention increased aerobic fitness and reduced body fat but not BMI in predominantly migrant preschool children. Trial registration Clinical Trials NCT00674544 .